Pelatihan Pengelolaan Kelompok Tani sebagai Wadah Peningkatan Produktivitas Usaha Tani di Desa Marga Cinta Kecamatan Moramo Kabupaten Konawe Selatan - Yusuf, Bakri; Bahtiar; Arsyad, Muhammad; Ridwan, Harnina; Suryani BB.; Jabar, Aryuni Salpiana (CV. Literasi Indonesia, 2022)
Farmer group management activities as a forum for increasing farming productivity aim to disseminate detailed and comprehensive information about the function of farmer groups in increasing farm productivity and to function of farmer groups as a social forum for farmers to increase farm productivity. Question and answer techniques are discussions, answer training and consultations. Although there are several inhibiting factors in the implementation of this activity, this training activity has a very good response and high enthusiasm from the participants, therefore this activity can make a very meaningful contribution to the community in the area of ​​activity, especially regarding the existence and function of farmer groups as farmers' social institutions to increase farm productivity, and effective farmer group management strategies to improve the farming businesses of their members.